Transcriptome Remodeling of Differentiated Cells during Chronological Ageing of Yeast Colonies: New Insights into Metabolic Differentiation - Wilkinson, Derek; Maršíková, Jana; Hlaváček, Otakar; Gilfillan, Gregor D; Ježková, Eva; Aaløkken, Ragnhild; Váchová, Libuše; Palková, Zdena (Oxidative medicine and cellular longevity, 2018)
We present the spatiotemporal metabolic differentiation of yeast cell subpopulations from upper, lower, and margin regions of colonies of different ages, based on comprehensive transcriptomic analysis. Furthermore, the analysis was extended to include smaller cell subpopulations identified previously by microscopy within fully differentiated U and L cells of aged colonies. New data from RNA-seq provides both spatial and temporal information on cell metabolic reprogramming during colony ageing and shows that cells at marginal positions are similar to upper cells, but both these cell types are metabolically distinct from cells localized to lower colony regions. As colonies age, dramatic metabolic reprogramming occurs in cells of upper regions, while changes in margin and lower cells are less prominent. Interestingly, whereas clear expression differences were identified between two L cell subpopulations, U cells (which adopt metabolic profiles, similar to those of tumor cells) form a more homogeneous cell population. The data identified crucial metabolic reprogramming events that arise de novo during colony ageing and are linked to U and L cell colony differentiation and support a role for mitochondria in this differentiation process.
Keywords: Saccharomyces cerevisiae; transkriptom; Transcriptome; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; Gene Expression Profiling; stanovení celkové genové exprese